2020
DOI: 10.4041/kjod.2020.50.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inclination and vertical changes between single-wire and double-wire retraction techniques in lingual orthodontics

Abstract: Objective: The Heat Induction Typodont System (HITS), used in some recent studies, has a distinct advantage over previous tooth movement simulation methods. This study aimed to compare inclination and vertical changes between the single-wire and double-wire techniques during en masse retraction with different lengths of lever arms in lingual orthodontics using an upgraded version of the HITS. Methods: Duet lingual brackets, which have two main slots, were used in this study. Forty samples were divided into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported the use of a few specific techniques to reduce the unexpected bowing effect and preserve the arch shape of the anterior six teeth during retraction: the reciprocal force applied to both the buccal and lingual sides of the bilateral canines, that is, ‘double cable’ mechanics, 16 placing the lever arms at the distal side of the canines, 10 or using a straight lingual ribbon‐wise archwire 21 . In our study, we used the double‐slot lingual bracket system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the use of a few specific techniques to reduce the unexpected bowing effect and preserve the arch shape of the anterior six teeth during retraction: the reciprocal force applied to both the buccal and lingual sides of the bilateral canines, that is, ‘double cable’ mechanics, 16 placing the lever arms at the distal side of the canines, 10 or using a straight lingual ribbon‐wise archwire 21 . In our study, we used the double‐slot lingual bracket system.…”
Section: Discussionmentioning
confidence: 99%